The Role of the Palatal Surgery in OSAS Treatment - Enöz, Murat (Fırat University, 2005)
The uvulopalatopharyngoplasty (UPPP) first described in 1981 by Fujita et al [], continues to be the mainstay for surgical treatment of OSA patient. . Since its introduction, there has been considerable effort expended studying the efficacy of this procedure and the role that it should play in the management of OSA. Unfortunately, the results of these studies have shown that UPPP as an isolated intervention for the treatment of OSA has met with mediocre results. Isolated UPPP has been shown to have limited success for treatment of OSA patients. In comparison, palatal procedures combined with other surgical approaches that address the multiple sites of obstruction in the upper aerodigestive tract seem to have improved success in the carefully selected patient. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Uvulopalatofarengoplasti (UPPP) ilk olarak 1981 yılında Fujita ve arkadaşları[] tarafından tanımlanmış ve obstrüktif sleep apne sendromu (OSAS) cerrahi tedavisinde başlıca temel teknik olarak kabul edilmiştir. Bu tekniğin ilk tanımlanmasından itibaren yöntemin sleep apne tedavisindeki etkinliği araştırılmıştır. Maalesef bu çalışmaların sonucunda tek başına UPPP' nin tedavideki etkinliğinin sınırlı olduğu görülmüştür. Tek başına UPPP, sleep apneli hastaların tedavisinde sınırlı başarı oranına sahiptir. Buna karşılık, özenle seçilmiş hastalarda, palatal prosedürler üst hava yolundaki obstrüksiyon yerlerine yönelik diğer cerrahi yöntemlerle kombine edildiğinde başarı oranı artmaktadır. ©2005, Fırat Üniversitesi, Tıp Fakültesi
OSAS Tedavisinde Palatal Cerrahinin Yeri